2016
DOI: 10.1596/1813-9450-7644
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impacts of Mais Educação on Educational Outcomes: Evidence between 2007 and 2011

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
0
16
0
2
Order By: Relevance
“…The results found in the existing literature do not indicate conclusive effects for the full-time school model; more time in school does not necessarily translate into student learning and performance. In Brazil particularly, more time in school with the federal program "More Education" is associated with negative effects in mathematics and Portuguese, as presented in Almeida et al (2016). Aquino and Kassouf (2011) also find that 9 th graders in full-time schools in São Paulo showed no significant differences in proficiency and pass rates in comparison to those who attended traditional schools.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The results found in the existing literature do not indicate conclusive effects for the full-time school model; more time in school does not necessarily translate into student learning and performance. In Brazil particularly, more time in school with the federal program "More Education" is associated with negative effects in mathematics and Portuguese, as presented in Almeida et al (2016). Aquino and Kassouf (2011) also find that 9 th graders in full-time schools in São Paulo showed no significant differences in proficiency and pass rates in comparison to those who attended traditional schools.…”
Section: Resultsmentioning
confidence: 98%
“…Using the methodologies of propensity score matching, panel data analysis, and DID, the authors find that 9 th graders in full-time schools showed no significant differences in proficiency (using the state system of external evaluation, SARESP) and pass rates in comparison to those who attended traditional schools. 16 Pereira (2011), Mendes (2011) and Almeida et al (2016) have evaluated the federal program "More Education", responsible for supporting states and cities in their intent to increase the number of school hours to at least 7 hours a day in public elementary, middle, and high schools in the capitals, in other cities of the nine Brazilian metropolitan areas, as well as in other cities with more than 90,000 inhabitants. Pereira (2011) uses DID methodology, designating the elementary and middle schools that had participated in the program in 2009 as the treatment group and the elementary and middle schools that only joined the program in 2010 as the control group.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that results can be achieved in a more cost effective way by exploiting the potential complementarity between non-monetary incentives and intrinsic motivation (Bowles and Polania-Reyes, 2012;Ashraf et al, 2014). However, complementing local capacity through technical assistance may be critical, as autonomy alone has had limited success in the Brazilian context (Almeida et al, 2016;Oliveira et al, 2016).…”
Section: Introductionmentioning
confidence: 83%
“…Finally, this paper also connects to works on the effects of lengthening the school day on non-criminal outcomes. Almeida et al (2016) use propensity score matching to assess the impact of early stages of Mais Educação on schooling outcomes and find negative impact on Math test scores. In addition to negative effects on crime, Berthelon and Kruger (2011) find that longer school days reduced the probability poor juveniles became adolescent mothers.…”
Section: List Of Tablesmentioning
confidence: 99%